Co-doped carbon materials synthesized with polymeric precursors as bifunctional electrocatalysts. Issue 59 (30th September 2020) - Karajagi, Imran; Ramya, K.; Ghosh, P. C.; Sarkar, A.; Rajalakshmi, N.
Abstract : Metal free bifunctional catalysts based on co-doped carbon materials synthesized from polymeric precursors via a simple pyrolysis route with high cyclic stability and low polarization for Zn–air batteries. Abstract : The design of stable and high performance metal free bifunctional electrocatalysts is a necessity in alkaline zinc–air batteries for oxygen reduction and evolution reaction. In the present work co-doped carbon materials have been developed from polymeric precursors with abundant active sites to achieve bifunctional activity. A 3-dimensional microporous nitrogen–carbon (NC) and co-doped nitrogen–sulfur–carbon (NSC) and nitrogen–phosphorus–carbon (NPC) were synthesized using poly(2, 5-benzimidazole) as an N containing precursor. The obtained sheet like structure shows outstanding ORR and OER performance in alkaline systems with excellent stability compared to Pt/C catalyst. The doped heteroatom in the carbon is expected to have redistributed the charge around heteroatom dopants lowering the ORR potential and modifying the oxygen chemisorption mode thereby weakening the O–O bonding and improving the ORR activity and overall catalytic performance. The bifunctional activity (Δ E = E j =10 − E 1/2 ) of an air electrode for NPC, NSC, NC and Pt/C is 0.82 V, 0.87 V, 1.06 V and 1.03 V respectively, and the NPC value is smaller than most of the reported metal and non-metal based electrocatalysts. The ORR (from onset potential) and OER (10 mA cm −2 ) overpotential for NPC, NSC, and NC is (290 mV, 410 mV), (310 mV, 450 mV) and (340 mV, 600 mV) respectively. In the prepared catalyst the NPC exhibited higher ORR and OER activity (NPC > NSC > NC). The doping of P in NPC is found to have a great influence on the microstructure and therefore on the ORR and OER activity.